Analysis of Functioning of the Regional Brand Vysočina Regional Product in the Globalized Environment - Kožená, Marcela; Brodský, Martin (Žilinská univerzita, 2018)
In the present days, there are many customers, who prioritize regional products. There are numerous reasons for this decision, greater trust in the quality of these products, support for local businesses, or an attempt to promote a given region. Regional labelling can help develop tourism in a given region, especially if it is a protected land area not affected by industrialization. However, the small businesses find themselves in a difficult situation to succeed in today's globalized market environment. The goal of this paper is to analyse how the regional label of Vysočina regionální produkt (Vysočina Regional Product) operates and to present proposals for developing this label using suitable marketing tools in the globalized environment. Labels have many important functions, for example, they help customers identify a product manufacturer or can provide positive or negative motivation to purchase a product, etc. The corporate goal is to represent a specific quality of products and services by the brand, causing return of satisfied customers, and thus ensure further business. Currently, there are dozens of regional labels in the Czech Republic; VYSOČINA regionální produkt®, is one of them. Compared to a number of other regional products, this brand also faces numerous problems, as these mostly small companies do not have sufficient funds and therefore are not able to promote their products. In this paper, a comparison of selected regional brands was conducted, including a customer questionnaire and a proposal for the use of marketing tools to ensure further development of the Vysočina regional product label.
Analýza fungování regionální značky Vysočina regionální produkt v globalizovaném prostředí
Keywords: regional product; globalization; labelling; company; customer; regionální produkt; globalizace; značení; podnik; zákazník